The plague of Christianity: religious dispute and pandemic in a fragment of Against the Christians, by Porphyry of Tyre - Romero, Sérgio Luiz Gusmão Gimenes (Revista Archai, 2026)
This work discusses the religious clash between Christians and Pagans in the 3rd century CE based on a fragment of Against the Christians, by Porphyry of Tyre, cited by Eusebius of Caesarea. The focus is on blaming Christians for the Crisis of the third century, specifically in relation to the Plague of Cyprian, a pandemic that devastated several regions of the Empire and strengthened hostility against adherents of the Christian faith. The notion of ideology is used as a category of analysis, considering the inseparable nexus between material and spiritual aspects of social life.